1985
DOI: 10.1002/jso.2930300215
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of bartholin's gland: Review of the literature and report of two cases

Abstract: Two patients with adenoid cystic carcinoma of Bartholin's gland and a review of the relevant literature are presented. With the inclusion of these two patients, there are now 24 cases reported. Both patients had large vulvar masses with a short clinical history, and several local tumor recurrences within the first 21/2 years after radical vulvectomy. The characteristic cribriform pattern and perineural involvement in addition to vascular invasion were present in the pathological material. No metastases were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…The tumor has a remarkable similarity to certain adenocarcinomas of the breast. In fact, some authors have reported that ACC is indistinguishable from ACC of the breast and vulva [1,2]. No standard histologic parameters have proven to be reliable markers of local recurrence or distant metastases in cases of ACC.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor has a remarkable similarity to certain adenocarcinomas of the breast. In fact, some authors have reported that ACC is indistinguishable from ACC of the breast and vulva [1,2]. No standard histologic parameters have proven to be reliable markers of local recurrence or distant metastases in cases of ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Data is lacking for the role of chemotherapy and biological treatment of BG-ACC. Few studies have trialled 5-fluorouracil, adriamycin, cyclophosphamide, cisplatin, CPT-11 (Irinotecan), methotrexate, and doxorubicin with varying efficacy [ 17 – 20 ]. A single patient trial of adjuvant Tamoxifen on metastatic BG-ACC delayed disease progression for 4 years while maintaining quality of life [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous management of lung metastasis showed that surgery alone was not sufficient [4]. Several chemotherapeutic regimens have been reported in the literature but the use of cyclophosphamide, adriamycin and cisplatin seems most common [4,11]. …”
Section: Discussionmentioning
confidence: 99%